Evaluación comparativa de metabolitos secundarios, actividad antimicrobiana y letalidad de extractos orgánicos de Cymbopongocicratus (Hierba Luisa) y Melissa officinalis (toronjil). - Vélez Rodríguez, Ruth Elizabeth (2015)
This research was based on a comparative analysis of secondary metabolites, antimicrobial and lethal activity of different extracts of Cymbopogon citratus (lemongrass) and Melissa officinalis (lemon balm). It began with a number of previously treated leaves and processed to prepare each extract using different solvents and perform the phytochemical screening, where the presence of sterols, triterpenes and mucilage was found in the hexane extract and coumarins, metilencetonas, sterols, triterpenes, phenylpropanoids , catechins and mucilage in the methanol extract of C. citratus. M.